Correlations of nanoscale film morphologies and topological confinement of three-armed cage block copolymers. Issue 23 (25th May 2021) - Ree, Brian J.; Satoh, Yusuke; Isono, Takuya; Satoh, Toshifumi
Abstract : Three-armed cage block copolymers composed of immiscible blocks in near equivalent volume fractions formed topologically controlled sub-10 nm cylindrical and lamellar nanostructures in nanoscale films. Abstract : The nanoscale film morphologies of three-armed cage block copolymers showing three different variations ( Cage -A, -B, and -C) have been investigated for the first time via synchrotron grazing incidence X-ray scattering. For all cage block copolymers, the individual block components revealed amorphous characteristics. Nevertheless, they all exhibited either cylindrical or lamellar phase-separated nanostructures. Key structural parameters such as domain spacing ( d -spacing), structural ordering, and orientation varied depending on the cage topologies. In particular, the d -spacing of nanostructures ranged from 6.50 to 10.85 nm. Compared to their linear block copolymer analogues, the cage block copolymers achieved a 54.8–74.5% d -spacing reduction. Overall, structural parameters such as d -spacing, structural ordering, and orientation were found to be correlated with the topological confinement which originated from the molecular cage topology.